Caring for COVID's emotional long haulers. Issue 3 (March 2022) - Tye, Joe; Long, Kimberly; Blake, Nancy; Luu, Allison; Tye, Annie
Abstract : 14 strategies to safeguard nurses' mental health Abstract : The COVID-19 pandemic has taken a toll on the emotional, psychological, and spiritual well-being of healthcare workers. This article presents 14 strategies nurse leaders can use to help safeguard nurses' mental health.